ISLAMISM AND THE EMERGENCE OF ISLAMIC POPULISM THE ROLE OF DA'WAH MEDIA IN MASS MOBILIZATION ON “BELA ISLAM” ACTION: CASE STUDIES OF DAKWAH SYARIAH RADIO (RDS FM) SOLO - Ari Alfiatul Rochmah (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract: This article aims to analyze the raft of Dakwah Syariah Radio (RDS FM) as one of the radio stations of Islamic radical movement in Solo, on mobilizing for the 'Bela Islam' actions both in Solo and Jakarta from Islamic Populism perspective. Vedi Hadiz defines Islamic populism as an asymmetrical social class movement, even with class interests that may be antagonistic and different levels of using Islam as a shared identity. To that end, the populist Islamic movement becomes a fairly recent phenomenon in which various Islamic organizations even from different platforms such as FPI, HTI, and MMI can move in a momentum. This article will examine how the RDS FM in its broadcast to mobilize participation in the anti-Ahok rally by looking at the broadcast, website, social media and brochure papers. By using qualitative method, this article try to analyze the data by deep interviewing the radio’s staffs and anchor, also the radio’s broadcast on air, on line, or by website and social media. This article argues that radicalization in a macro level such as economic and political repression, can provoke radical Muslim euphoria to the local and global history of Islamist movements by using the rhetoric of religion and the enforcement of Islamic Shari'ah to fight 'the kafir', as well as opposing the leadership of Basuki T. Purnama which is non-Muslim. Through the perspective of Islamic-populism, the politial and religious actors also use the media like radia by its broadcast and social in the process of mass moilization.Keyword: Islamic Populism; Media; Islamism; radicalism; RDS FM; Solo. Abstrak. Artikel ini bertujuan untuk menganalisis siaran Radio Dakwah Syariah (RDS FM) sebagai salah satu stasiun radio gerakan radikal Islam di Solo, dalam menggalang aksi ‘Bela Islam’ baik di Solo maupun Jakarta dari perspektif Populisme Islam. Vedi Hadiz mendefinisikan populisme Islam sebagai gerakan kelas sosial yang asimetris, bahkan dengan kepentingan kelas yang mungkin bersifat antagonis dan tingkatan yang berbeda dalam menggunakan Islam sebagai identitas bersama. Untuk itu, gerakan Islam Populis menjadi fenomena yang cukup mutakhir di mana berbagai ormas Islam bahkan dari platform yang berbeda seperti FPI, HTI, dan MMI dapat bergerak dalam suatu momentum. Artikel ini akan mengkaji bagaimana RDS FM dalam siarannya memobilisasi partisipasi dalam unjuk rasa anti-Ahok dengan melihat siaran, situs web, media sosial, dan kertas brosur. Dengan menggunakan metode kualitatif, artikel ini mencoba menganalisis data dengan melakukan wawancara mendalam kepada staf dan penyiar radio, juga siaran radio di udara, online, atau melalui situs web dan media sosial. Artikel ini berpendapat bahwa radikalisasi di tingkat makro seperti represi ekonomi dan politik, dapat memancing euforia Muslim radikal terhadap sejarah lokal dan global gerakan Islam dengan menggunakan retorika agama dan penegakan syari’at Islam untuk melawan 'kafir'. , serta menentang kepemimpinan Basuki T. Purnama yang non-Muslim. Melalui perspektif populisme-Islam, para pelaku politik dan agama juga menggunakan media seperti radia dalam penyiarannya dan sosial dalam proses moilisasi massa.Kata Kunci: Populisme Islam; Media; Islamisasi; Radikalisme; RDS FM; Solo.